2017
DOI: 10.1016/j.aap.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Gender roles, sex and the expression of driving anger

Abstract: The present study investigated the validity of the 25-item Driving Anger Expression Inventory (DAX) as well as the role of sex and gender-roles in relation to the expression of driving anger in a sample of 378 French drivers (males=38%, M=32.9years old). Confirmatory Factor Analysis supported the four-factor structure of the 25-item DAX (Adaptive/Constructive Expression; Use of the Vehicle to Express Anger; Verbal Aggressive Expression and Personal Physical Aggressive Expression) and two of the three aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
5
12
0
3
Order By: Relevance
“…DAS, DAX, DDDI and other related instruments had also been used for the analysis of drivers response according to gender, age and work conditions [22,23,29,34,[46][47][48][49][50][51][52][53][54][55][56][57][58]. For example, Sullman found that females display a higher level of anger due to risky driving on the 33-items DAS survey [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAS, DAX, DDDI and other related instruments had also been used for the analysis of drivers response according to gender, age and work conditions [22,23,29,34,[46][47][48][49][50][51][52][53][54][55][56][57][58]. For example, Sullman found that females display a higher level of anger due to risky driving on the 33-items DAS survey [48].…”
Section: Introductionmentioning
confidence: 99%
“…For the DAX survey, several works have been performed studying the differences in the expression of anger between males and females [49][50][51][52][53]. For example, Eşiyok, Yasak, and Korkusuz found that males between 21 and 30 years report a higher expression of anger through physical means compared to other age groups [51].…”
Section: Introductionmentioning
confidence: 99%
“…Extended versions of the TBP have also highlighted the role of injunctive, descriptive, personal and moral norms in predicting such behaviours (e.g., Cestac, Paran, & Delhomme, 2011, 2014Cooke, Dahdah, Norman, & French, 2016;Elliott, Armitage, & Baughan, 2003;. Also, research on the psychosocial determinants of aberrant driving behaviours have investigated the influence of sex roles, gender stereotypes (Degraeve, Granié, Pravossoudovitch, & Lo Monaco, 2015;Granié, 2009;Özkan & Lajunen, 2005;Pravossoudovitch, Martha, Cury, & Granié, 2015;Sullman, Paxion, & Stephens, 2017) and that of such personality traits as aggressive behaviours (Lajunen, Parker, & Stradling, 1998), sensation seeking (Iversen & Rundmo, 2004;Ulleberg & Rundmo, 2003), empathy and conformity (Nordfjaern & Şimşekoğlu, 2014). More recently, Nordfjaern and colleagues have questioned the role of cultural factors in determining risky behaviours for both pedestrians (Nordfjaern & Şimşekoğlu, 2013;Nordfjaern & Zavareh, 2016) and drivers (Nordfjaern & Şimşekoğlu, 2014) in Middle East .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complexity of the human behavior mechanism, there is still a lack of driving behavior prediction algorithms that can be applied to vehicle intelligence systems. In recent years, researchers argued that driver’s affective factors have close associations with road accidents [ 10 , 11 ]. Psychologists now widely accept that it is impossible for people to think or perform an action without engaging their emotional system, at least unconsciously [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%